Some Medicinal Aromatic Plants Sold by Kastamonu Herbalists and Usage Areas - Kavaklı, Seydi Ahmet; Yaylacı, Şahin Gürkan; Ugurlu, Emin (Igdir University, 2020)
In this study, a total of seven herbalist, one female, between 31-58 years old, who were selling in Kastamonu city center, Tosya and Taşköprü districts, were interviewed. The information about the local names, usege areas, parts of use, and types of herbal drugs sold were taken from the herbalists. The collected data are presented in a chart by comparing it with the literature. According to the result, sixty-six taxa belonging to thirty-three families, which are sold in herbalists, were determined. The family with the most taxa is Rosaceae family with eight taxa (22%), followed by Lamiaceae with six taxa (17%), Apiaceae, Asteraceae and Fabaceae families with five taxa (14%) respectively. According to the information obtained from the herbalists, twenty-four taxa (31%) and the most used drog part are the leaves. This is followed by fruit with twenty taxa (%26), flower with twelve taxa (15%), root with seven taxa (9%), seed, bark and stem with four taxa (5%), leafy and flowering branches with two taxa (3%) and rosin with one taxon (1%) respectively. Infusion method with thirty-nine taxa (50%) is at the top of the usage of taxa, sixteen taxa (21%) raw consumption, twelve taxa (15%) decoction (decoction), nine taxa (12%) powder and one taxa (1%) are followed by melting and burning methods respectively.

Bu araştırmada Kastamonu il merkezi, Tosya ve Taşköprü ilçelerinde satış yapan 31-58 yaşları arasında, biri kadın olmak üzere toplam yedi aktarla görüşülmüştür. Satılan bitkisel drogların yöresel isimleri, kullanım alanları, kullanılan kısımları, kullanım şekillerine ait bilgileri aktarlardan alınmıştır. Toplanan bilgiler, literatür bilgileri ile karşılaştırılarak çizelge halinde verilmiştir. Araştırma sonucunda aktarlarda satılan otuz üç familyaya ait cins ve tür düzeyinde altmış altı takson belirlenmiştir. En çok taksona sahip familya sekiz takson (%22) ile Rosaceae familyasıdır, onu sırasıyla altı takson (%17) ile Lamiaceae, beşer takson (%14) ile Apiaceae, Asteraceae ve Fabaceae familyaları takip etmektedir. Aktarlardan elde edilen bilgiye göre yirmi dört takson (%31) ile en çok kullanılan drog kısmı yapraklardır. Bunu sırasıyla yirmi takson (%26) ile meyve, on iki takson (%15) ile çiçek, yedi takson (%9) ile kök, dörder takson (%5) ile tohum, kabuk ve sap, iki takson (%3) ile yapraklı ve çiçekli dallar ve bir takson (%1) ile reçine takip etmektedir. Taksonların kullanım şekillerinin başında otuz dokuz takson (%50) ile demleme (infüzyon) yöntemi gelmektedir, onu sırasıyla on altı takson (%21) çiğ tüketim, on iki takson (%15) kaynatma (dekoksiyon), dokuz takson (%12) toz ve birer takson (%1) ise eritme ve yakma yöntemleri ile tüketim takip etmektedir.
Kastamonu Aktarlarında Satılan Bazı Tıbbi Aromatik Bitkiler ve Kullanım Alanları
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği